Religious Moderation in KPSAR: A Van Dijk’s Critical Discourse Analysis - Malik, Muhammad Ardiansah Maulana; Wirajaya, Asep Yudha (Buletin Al-Turas, 2025)
PurposeThis research aimed to analyze the concept of religious moderation in KPSAR using Van Dijk's Critical Discourse Analysis approach and religious moderation. MethodThis research used a qualitative case study method, relying on document analysis as the main data source. Data were collected from the original text of KPSAR that was written in Jawi (Malay Arabic) script, then analyzed by focusing on text structure, social context, and cognitive process. Results/findingsKPSAR reflected the values of religious moderation through emphasis on the concept of tawhid, the obligatory attributes of Allah and Rasulullah, as well as systematic faith teachings. It presented an inclusive theological understanding, integrating local traditions and Islamic principles to avoid extremism. It also revealed that the text structure of the book is systematic, starting from the opening, main content, to the conclusion that highlights the value of social harmony and respect for diversity. ConclusionKPSAR not only functioned as a theological guide but also as an educational tool that strengthened religious moderation that was relevant in the socio-religious context of pluralistic societies.